2022
DOI: 10.1007/s10706-022-02269-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Stone and Deep Mixing Lime Columns on Stability of Embankments Constructed on Soft Consolidating Soil

Abstract: One of the most common, effective and innovative ways to improve soft soil is to use stone columns or lime columns. An extensive study has been conducted to find the effectiveness of lime or stone columns to improve the settlement of embankments constructed over soft consolidating soil. There are very few studies to evaluate the effects of columns on embankment safety factor during foundation soil consolidation. This study examined the effectiveness of stone and lime columns on the embankment stability, both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, Prakash and Krishnamurthy (2022) [19] reported that combining SC and DMC enhances safety, reduces consolidation settlement, and provides drainage performance similar to SCs.…”
Section: Ramadan Et Al (2022)mentioning
confidence: 99%
“…Additionally, Prakash and Krishnamurthy (2022) [19] reported that combining SC and DMC enhances safety, reduces consolidation settlement, and provides drainage performance similar to SCs.…”
Section: Ramadan Et Al (2022)mentioning
confidence: 99%
“…DSM is an in situ ground improvement technique that enhances the parameters of a weak subsoil by introducing a hydraulic binder into its structure, e.g., lime [8][9][10], cement [11][12][13][14][15][16], fly ashes [17][18][19][20], or a combination of different types of binders and activators [21][22][23]. It must be noticed here that the issue of this study is very much related to the production of backfill materials for the mining industry.…”
Section: Introductionmentioning
confidence: 99%